Väyrysen ja Kääriäisen korkean profiilin aika 1981‒1991 Keskustan historia 6 - Katajisto, Kati (Historiallinen Arkisto, 2023)
The Centre Party of Finland was represented in almost all cabinets for decades, and it often held the post of prime minister during the reign of President Urho Kekkonen. When Kekkonen's deteriorating health forced him to resign in 1981, the Centre Party, formerly the Agrarian Union, was in front of the crisis. The party was deeply divided along the lines of who would be the best candidate to succeed Kekkonen. The schism had prevailed for years, and contemporaries suspected the party would split up or at least lose its dominant position in Finnish politics. Besides, the numbers of core supporters making up the party, agrarians, were constantly diminishing. In addition, the Finnish party system was in a state of flux. The Finnish People's Democratic League was in a deep downward spiral, while the Conservative Party's support was ascendant. The power struggle between the three 'big' parties, the Centre Party, the Social Democratic Party and the Conservative Party, was fierce. The study describes and analyses how the Center Party survived the challenges it faced. How was the cohesion of the party rebuilt and maintained? How did the Centre Party manage to survive the inter-party contests and end up being the strongest party in the elections of 1991? The study is firmly based on source material from the party organization of the Centre Party and other relevant political actors, such as President Mauno Koivisto. The book provides new information on both Finnish domestic and foreign politics and the power struggles among the parties and leading political figures.